Dendrite-free lithium electrodeposition enabled by 3D porous lithiophilic host toward stable lithium metal anodes. Issue 1 (11th November 2021) - Xu, Linghong; Yu, Zhihao; Zheng, Junrong
Abstract: Lithium metal is a promising anode utilized in cutting-edge high-energy batteries owing to the low density, low electrochemical potential, and super high theoretical capacity. Unfortunately, continuous uncontrollable lithium dendrite growth and 'dead' lithium result in capacity decay, low coulombic efficiency and short circuit, severely hindering the practical utilization of lithium anode. Herein, we propose a three-dimensional porous lithiophilic current collector for lithium storage. The conductive 3D structure constructed by carbon fiber (CF) can well accommodate the deposited lithium, eliminating volume change between the lithium depositing/stripping process. Moreover, the polydopamine (PDA) coating on the CF surface possesses a large number of polar groups, which can homogenize Li + ions distribution and apply as the sites for lithium deposition, decreasing nucleation overpotential. As a result, under the 1 mA cm −2 current density, the PDA coated CF (PDA@CF) electrode exhibits high CE (∼98%) for 1000 cycles. Galvanostatic measurements demonstrate that the Li anode using PDA@CF achieves 1000 h cycling life under 1 mA cm −2 with a low overpotential (<15 mV). The LiFePO4 full cell shows enhanced rate performance and stable long-term cycling.